2015
DOI: 10.1099/jgv.0.000275
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolomics profiling for the prediction of cytomegalovirus DNAemia and analysis of virus–host interaction in allogeneic stem cell transplant recipients

Abstract: Metabolomics analysis of biofluids is increasingly being recognized as a useful tool for the diagnosis and management of a number of infectious diseases. Here we showed that plasma metabolomics profiling by untargeted 1 H nuclear magnetic resonance may allow the anticipation of the occurrence of cytomegalovirus (CMV) DNAemia in allogeneic stem cell transplant. For this purpose, key discriminatory metabolites were total glutathione, taurine, methylamine, trimethylamine N-oxide and lactate, all of which were upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
2
2
Order By: Relevance
“…We tested the associations of 12 metabolite measures, and only TMAO, which correlated inversely with CMV infection, was found to be associated. This result contradicts the previous findings acquired in the study by Monleón et al 2015 [ 15 ], where higher levels of TMAO were associated with CMV infection in aHSCT patients after transplantation. These differences in results could be due to variations in the studies’ setups (Monleón et al [ 15 ] measured TMAO post-CMV infection onset), the small cohort sizes (59 patients were included in the previous study, and 68 patients were included in our study), or unexplored confounding factors (e.g., haematological malignancy, diet, or other lifestyle-related variables).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We tested the associations of 12 metabolite measures, and only TMAO, which correlated inversely with CMV infection, was found to be associated. This result contradicts the previous findings acquired in the study by Monleón et al 2015 [ 15 ], where higher levels of TMAO were associated with CMV infection in aHSCT patients after transplantation. These differences in results could be due to variations in the studies’ setups (Monleón et al [ 15 ] measured TMAO post-CMV infection onset), the small cohort sizes (59 patients were included in the previous study, and 68 patients were included in our study), or unexplored confounding factors (e.g., haematological malignancy, diet, or other lifestyle-related variables).…”
Section: Discussioncontrasting
confidence: 99%
“…This result contradicts the previous findings acquired in the study by Monleón et al 2015 [ 15 ], where higher levels of TMAO were associated with CMV infection in aHSCT patients after transplantation. These differences in results could be due to variations in the studies’ setups (Monleón et al [ 15 ] measured TMAO post-CMV infection onset), the small cohort sizes (59 patients were included in the previous study, and 68 patients were included in our study), or unexplored confounding factors (e.g., haematological malignancy, diet, or other lifestyle-related variables). TMAO is formed from trimethylamine (TMA), which is produced by the gut microbiota following dietary intake of choline, phosphatidylcholine, and L-carnitine [ 24 , 25 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, because of the limitations of the GC-MS platform, VLCFAs were not detected in this study. According to the results of our study and those of previous HCMV-related clinical metabolic studies, although the content of total fatty acid increased, specific fatty acids showed an increasing or decreasing trend 35 . Thus, we hypothesised that HCMV up-regulated specific VLCFAs for incorporation into the viral envelope.…”
Section: Discussionsupporting
confidence: 79%